Women on Board and Firm Financial Performance - Fitri, Hotma Rahma (2009)
Board diversity is one among factors from the Good Governance Internal Mechanisms. From corporate governance perspective, the board diversity will enhance the firm performance. Gender diversity as the one among factors that is required since the rising amount of women in this 21st century; that the nation needs to empower women's ability to enhance its' economic ability. Without developing and empowering women, their big amount only becomes a burden to the nation. Indonesia is a country that adopts strong patriarchal system and under this system hiring women becomes unfavorable factor to do, especially at the strategic level like on Board Room. Tokenism is the popular reason for a firm to hire women on board to avoid punishment from government. But this reason raises the question to whether women performances really have a positive affect to the firm's financial performance or just a "make up" strategy without any positive effect to firm financial performance itself. This thesis reviews corporate governance point of view about gender diversity specifically women presence on board room and their effect to firm financial performance. These reviews include some recent researches about women on board room in international level and a little evidences and previous research about women presence in Indonesia. To date, however, only a limited number of studies on women presence on board room are available, especially in Indonesia setting. This study seeks for the answer whether or not ratio of women on board affects the firm financial performance. The women presences on board room have measured by three ratios namely: women presence on board of commissioner; women presence on board of director/board of executive; and women presence on audit committee. The evidences from 205 companies listed in Jakarta Stock Exchange Indonesia in 2007 have founded that either women have been hired based on tokenism or not, and the following are the results: 1. Ratio of women on audit committee is significantly positive to ROA. 2. Ratio of women on board of commissioner is insignificantly positive to ROA. 3. Ratio of women on board of executive/ board of director is insignificantly negative to ROA.